Acute sleep responses in a normobaric hypoxic tent - Pedlar, C.; Whyte, G.; Emegbo, S.; Stanley, N.; Hindmarch, I.; Godfrey, R. (Medicine & Science in Sports & Exercise, 2005)
Purpose: Sleeping in a hypoxic environment is becoming increasingly popular among athletes attempting to simulate a "live high, train low" training regime. The purpose of this study was to investigate the acute effects (one night) of sleeping in a normobaric hypoxic tent (NH) (PO2 = 110 mm Hg [almost equal to] 2500 m) upon markers of sleep physiology and quality, compared with sleep in a normal ambient environment (BL) (PO2 = 159 mm Hg [almost equal to] sea level) and sleep in a normobaric normoxic tent (NN) (PO2 = 159 mm Hg).